North Macedonia : Technical Assistance Report - Public Expenditure and Financial Accountability Performance Assessment. (IMF Staff Country Reports; Country Report ;, 2022)
This PEFA assessment provides a snapshot of the country's PFM system performance in order to support the government in defining PFM reform priorities. The previous assessment was conducted in 2015, therefore the current assessment follows after the recommended time period between the two assessments. Furthermore, the scope and objectives of the reforms initiated and implemented in the intervening period makes tracking the change in the PFM system needed and meaningful. The assessment was conducted by the International Monetary Fund and the World Bank, with the Ministry of Finance and other relevant country institutions being the primary beneficiaries of the assessment.